2020
DOI: 10.1542/hpeds.2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Content of Pediatric Discharge Summaries

Abstract: OBJECTIVES: The need for high-quality discharge summaries is critical to ensure safe transitions of care. Deficits may lead to lapses in communication and poor outcomes. In this study, we sought to characterize the completeness, accuracy, and quality of pediatric discharge summaries. METHODS: A retrospective chart review of 200 discharge summaries of patients discharged from the general pediatrics service from July 2016 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Investigators developed a hands-on educational session for house staff, which included: (1) a didactic portion on the history and importance of the transition of care communication/documentation; (2) presentation of local data obtained via a needs assessment 10 ; and (3) an interactive small-group workshop where trainees evaluated de-identified discharge summaries based on the standardized rubric and discussed specific feedback to improve quality. This session was delivered by three faculty members and one senior resident during a 1-hour protected conference time slot at the start of each training year.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigators developed a hands-on educational session for house staff, which included: (1) a didactic portion on the history and importance of the transition of care communication/documentation; (2) presentation of local data obtained via a needs assessment 10 ; and (3) an interactive small-group workshop where trainees evaluated de-identified discharge summaries based on the standardized rubric and discussed specific feedback to improve quality. This session was delivered by three faculty members and one senior resident during a 1-hour protected conference time slot at the start of each training year.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome measure was the percentage of selected discharge summaries in a 2-week period that contained all three required elements: discharge diagnosis, discharge medications, and follow-up appointments. The investigators chose these three elements after baseline data review 10 revealed the greatest opportunity to improve these essential elements of discharge summaries within the current EHR template. 8 As a balancing measure, investigators recorded delays in discharge summary completion: the number of discharge summaries that house staff completed after the date of discharge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Most patient-and caregiver-centered discharge summary tools use evidence-based techniques such as plain language, large fonts, 23 pictograms, 24 and teach-back components 25,26 to ensure patients are engaged and develop a strong understanding of their health. 27 While written patient-centered discharge tools have become commonplace in surgical, 28 rehabilitation, 29 and pediatric settings, 30 few have been employed in critical care settings. 31 To address the need for a standardized, written, patient-centered discharge tool suitable for use in the ICU, our team of patient partners (i.e., previous patients and family-caregivers who now represent patients' interest in research), clinicians, and researchers aimed to incorporate ICU-speci c elements into the Patient Oriented Discharge Summary (PODS) tool co-developed by patients, the Toronto Central Local Health Integration Network, and OpenLab (Toronto, Canada).…”
mentioning
confidence: 99%